Miejsce partii komunistycznej na „czerwonym” Uniwersytecie Marii Curie-Skłodowskiej w latach 1944–1989 - Gałaszewska-Chilczuk, Dorota (Pamięć i Sprawiedliwość, 2008)
This article is the result of several years of research in the state archives. The author tried to show the actual position, fi rst of the Polish Workers’ Party, and then of the Polish United Workers’ Party at the Maria Curie-Skłodowska University in Lublin. It was the fi rst state institution of higher learning created by the communist authorities, already in August 1944. The authorities wanted a model univeristy thatwould be not merely a forge for new academic and party cadres, but also the birthplace of a new intelligentsia, with a prefered worker or peasent background.The realization of these ambitions by the party turned out to be full of obstacles and pitfalls. The school’s party activists, due to the frequent lack of interest on the part of the central authorities, had huge difficulties in giving the school an image worthy of the tradition of the Polish Committee of National Liberation (PKWN). One must rememberthat the univeristy was founded on paper, without any material or didactical base.This child of the PKWN was treated instrumentally, according to their immediate needs, by the communists themselves. The authorities de facto remembered the existence of the UMCS when they were beginning the battle against the Catholic University of Lublin (KUL). The use of the UMCS by propaganda, precisely as avanguard against the Catholic school, determined its ‘red’ image.